Structure de la consommation de lait en Afrique de l'Ouest - Seyoum, Solomon (CIPEA, 1988)
Looks into the patterns of consumption of dairy products in West Africa. Discusses trends in production, imports. Examines factors influencing dairy consumption patterns, particularly population growth, urbanization, incomes, consumer preferences and prices.